Risk of cataract after exposure to low doses of ionizing radiation: A 20-year prospective cohort study among US radiologic technologists - BEKİROĞLU, GÜLNAZ NURAL (OXFORD UNIV PRESS INC, 2008)
The study aim was to determine the risk of cataract among radiologic technologists with respect to occupational and nonoccupational exposures to ionizing radiation and to personal characteristics. A prospective cohort of 35,705 cataract-free US radiologic technologists aged 24-44 years was followed for nearly 20 years (1983-2004) by using two follow-up questionnaires. During the study period, 2,382 cataracts and 647 cataract extractions were reported. Cigarette smoking for >= 5 pack-years; body mass index of >= 25 kg/m(2); and history of diabetes, hypertension, hypercholesterolemia, or arthritis at baseline were significantly (p <= 0.05) associated with increased risk of cataract. In multivariate models, self-report of >= 3 x-rays to the face/neck was associated with a hazard ratio of cataract of 1.25 (95% confidence interval: 1.06, 1.47). For workers in the highest category (mean, 60 mGy) versus lowest category (mean, 5 mGy) of occupational dose to the lens of the eye, the adjusted hazard ratio of cataract was 1.18 (95% confidence interval: 0.99, 1.40). Findings challenge the National Council on Radiation Protection and International Commission on Radiological Protection assumptions that the lowest cumulative ionizing radiation dose to the lens of the eye that can produce a progressive cataract is approximately 2 Gy, and they support the hypothesis that the lowest cataractogenic dose in humans is substantially less than previously thought.
Keywords: cataract; radiation; technology; radiologic; x-rays; ATOMIC-BOMB SURVIVORS; BODY-MASS INDEX; LENS OPACITIES; EPIDEMIOLOGIC ASSOCIATIONS; LENTICULAR OPACITIES; GAMMA-RADIATION; EYE CARE; HEALTH; POPULATION; SURGERY